THE EFFECTIVENESS OF THE IMPLEMENTATION OF ONLINE ENGLISH LEARNING DURING THE COVID-19 PANDEMIC ERA OF THE EIGHTH GRADE STUDENTS AT STATE JUNIOR HIGH SCHOOL 2 OF RAMBANG NIRU MUARA ENIM - Anzal Fajariah (Universitas PGRI Palembang, 2021)
This study aims to determine the effectiveness of online learning in learning English in the eighth grade students at state Junior High School 2 of Rambang Niru, Muara Enim. The questions are the questions that this research may try to answer: 1)How is the implementation of online English learning during the Covid-19 pandemic era at the eighth grade?2)How is the effectiveness of online English learning perceived by students, teachers and parents in English learning during the Covid-19 pandemic era 3) What are the drawbacks of the effectiveness of online learning perceieved by at the eighth grade ?This research using the Qualitatif method. The findings of this study found the ineffectiveness of online English learning.